KINERJA PEGAWAI DALAM PELAYANAN SERTIFIKAT TANAH PADA KANTOR PERTANAHAN KOTA BENGKULU - Andriani, Fitri (Jurnal Governance dan Administrasi Publik, 2017)
This study aims to determine the performance of employees in land certificate services at the Bengkulu City Land Office. One of the services provided by the public bureaucracy is land certification services, considering that the right to own land is one of the rights owned by humans. The problems faced by the Bengkulu City Land Office are almost the same as other Land Offices. The most prominent problem is the problem of the settlement of pearland sertifikatannot in accordance with the number of applications per year with a predetermined time schedule. This is because the procedure is long and takes a long time. The problems and complaints raised above in the processing of land certificates made the author interested in examining the performance of employees in land certificate services at the Bengkulu City Land Office, as the main reason for the desire of people who want to get fast service according to the service schedule without any complicated processes. -circular. The performance of Bengkulu City Land Office Employees in this study is discussed in four aspects including work accuracy and work quality; level of ability at work; ability to analyze data / information, and ability to use machines / equipment; and the ability to evaluate.